2017
DOI: 10.3892/ol.2017.6194
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated expression of MMP-9 in gingival epithelial cells induced by prolonged stimulation with arecoline

Abstract: Abstract. Betel quid chewing is implicated in the high prevalence of oral cancer in Southeast Asian countries. One of the major components of betel quid is arecoline. In the present study, in order to characterize the association between chronic arecoline stimulation and carcinogenesis the expression level of matrix metalloproteinase (MMP)-2, MMP-9, tissue inhibitor of metalloproteinase (TIMP)-1 and TIMP-2 mRNA in human gingival epithelial progenitor cells (HGEPs) stimulated with arecoline was assessed. The HG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Therefore, we employed an in vitro model of a daily BQ chewing habit that we showed previously to contain hypermethylated genes [23]. The cells were stimulated with arecoline, a major component of BQ, for a prolonged period according to our previous protocol [24]. We confirmed that significantly high level of methylation of SIRT1 was observed followed by downregulated expression of SIRT1 transcription and protein expression.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Therefore, we employed an in vitro model of a daily BQ chewing habit that we showed previously to contain hypermethylated genes [23]. The cells were stimulated with arecoline, a major component of BQ, for a prolonged period according to our previous protocol [24]. We confirmed that significantly high level of methylation of SIRT1 was observed followed by downregulated expression of SIRT1 transcription and protein expression.…”
Section: Discussionsupporting
confidence: 54%
“…Following overnight incubation, the HGEPs were treated with arecoline at a concentration of 50 μg/mL. The concentration of arecoline used in this study was as described in previous experiments [24]. Briefly, arecoline at the concentration of 50 μg/mL had no cytotoxic effect on the cells stimulated, even for a prolonged period, the method of alternating between 3 days with 50 μg/mL of arecoline and 3 days without arecoline for 1 month was selected.…”
Section: Cell Culture and Arecoline Exposurementioning
confidence: 99%
“…It binds to the promoter region of MMP-9 (matrix metalloproteinase-9) and inhibits its expression in endothelial cells (61). Expression and activity levels of MMP-9 was significantly upregulated in primary keratinocytes derived from healthy gingival epithelium treated with arecoline (62). MMP-9 also shows positive stromal expression in OSF cases (63).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our group evaluated a significant association between arecoline and the expression of SIRT1 in oral epithelial cells. Arecoline, the major alkaloid in betel quid, has been reported to be involved in the pathogenesis of oral cancer by facilitating the cellular transformation and transcriptional repression of tumour suppressor genes (TSGs) (10,45,46). We discovered that arecoline significantly induced DNA hypermethylation, followed by downregulation of SIRT1 expression in oral epithelial cells.…”
Section: Modulation Of Sirt1 In Oral Cancermentioning
confidence: 91%
“…Reactive oxygen species (ROSs) are the strongest risk factor associated with the pathogenesis of oral cancer (10). Habits such as betel quid chewing have been reported to induce generation of ROSs in the oral epithelium and lead to genetic instability by damaging DNA and other macromolecules (10,45). SIRT1 has been shown to increase the synthesis of antioxidant enzymes such as glutathione and superoxide dismutase 2 and prevent ROS-mediated genomic alterations (73).…”
Section: Future Research Perspectives and Possible Therapeutic Applicmentioning
confidence: 99%